CONUT Score as a Potential Nutritional Index for Predicting Mortality among Septic Patients - Altuntas, Gulsum; Timurkaan, Mustafa; Aksu, Ahmet; Dogan, Furkan; Demirel, Oguzhan (Anestezi Dergisi, 2025)
Objective: In sepsis patients, impairment of the immune system can damage the ability of fighting infection, and leads to poor outcomes. The aim of our study is to evaluate the role of the Controlling Nutritional Status (CONUT) score in predicting mortality in sepsis patients, in comparison with other nutritional assessment tools and disease severity scoring systems in intensive care units. Method: In this retrospective single-centre observational study patients aged ≥18 years who were followed up in intensive care units with a diagnosis of sepsis between January 2016 and October 2024 were included. Data was obtained from files and the hospital’s electronic database. Demographic data, laboratory parameters, Acute Physiology and Chronic Health Evaluation II (APACHE II) score, Sequential Organ Failure Assessment (SOFA) score, Nutritional Risk Screening 2002 (NRS 2002), and CONUT scores were recorded. Logistic regression analysis and multivariate modeling were performed to calculate the risk of mortality. The accuracy of APACHE II, SOFA, NRS 2002, and CONUT scores in predicting mortality was compared by receiver-operating characteristic (ROC) curves. Results: The study included 926 patients. In logistic regression analysis, SOFA, CONUT, APACHE II, and NRS 2002 Scores were independent risk factors. The CONUT score (AUC: 0.974), SOFA score (AUC: 0.964) and APACHE II score (AUC: 0.938) showed higher diagnostic accuracy than the NRS 2002 score (AUC: 0.814). There was no significant difference between CONUT and SOFA scores (p=0.37; z=1.48). CONUT score had a higher AUC than APACHE II (p<0.05; z=4.15). Conclusion: The CONUT score offers a practical alternative to clinicians, especially in assessing nutritional status and predicting mortality in patients with sepsis, due to its easy applicability and reliance on biochemical parameters. © This work is licensed by “Creative Commons Attribution-NonCommercial-4.0 International (CC)”.
Septik Hastalarda Mortaliteyi Öngörmede Potansiyel Bir Nutrisyonel İndeks Olarak CONUT Skoru
Keywords: Conut Score; Malnutrition; Mortality; Nrs 2002 Score; Sepsis